2016
DOI: 10.1111/jpi.12308
|View full text |Cite|
|
Sign up to set email alerts
|

Melatonin inhibits MMP‐9 transactivation and renal cell carcinoma metastasis by suppressing Akt‐MAPKs pathway and NFκB DNA‐binding activity

Abstract: Renal cell carcinoma (RCC) is the most lethal of all urological malignancies because of its potent metastasis potential. Melatonin exerts multiple tumor-suppressing activities through antiproliferative, proapoptotic, and anti-angiogenic actions and has been tested in clinical trials. However, the antimetastastic effect of melatonin and its underlying mechanism in RCC are unclear. In this study, we demonstrated that melatonin at the pharmacologic concentration (0.5-2 mm) considerably reduced the migration and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
104
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 139 publications
(114 citation statements)
references
References 58 publications
6
104
0
4
Order By: Relevance
“…Treatment with melatonin at a concentration of 2 mM was demonstrated to increase expression of p-p38 and p-JNK proteins. Previous immunofluorescence studies of p65-stained cells in addition to results of the present study, have suggested that 1-2 mM melatonin inhibits the translocation of NF-κB-p65 from the cytoplasm to the nucleus (28)(29)(30). These results correspond with the findings of the current study that melatonin markedly decreased cell viability and induced apoptosis in SGC7901 cells.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Treatment with melatonin at a concentration of 2 mM was demonstrated to increase expression of p-p38 and p-JNK proteins. Previous immunofluorescence studies of p65-stained cells in addition to results of the present study, have suggested that 1-2 mM melatonin inhibits the translocation of NF-κB-p65 from the cytoplasm to the nucleus (28)(29)(30). These results correspond with the findings of the current study that melatonin markedly decreased cell viability and induced apoptosis in SGC7901 cells.…”
Section: Discussionsupporting
confidence: 83%
“…The potential to target the mechanisms that inhibit NF-κB-p65, and promote p38 and JNK, may provide a strategy to investigate the efficacy of a number of types of chemotherapy. Similar studies in other types of tumor may provide useful data on the cellular response to melatonin that inhibits cell survival (26,28). The results of the present and previous studies lead to the hypothesize that melatonin induces apoptosis and oncostasis via the modulation of the JNK, p38 and NF-κB-p65 signaling pathways.…”
Section: Discussionmentioning
confidence: 54%
“…Similarly, epigallocatechin-3-gallate, a water-soluble flavonoid, reduces the viability, induces apoptosis, and suppresses the invasion and migration of RCC cells by down-regulation of MMP-2 and MMP-9 [35]. Melatonin also has anti-metastatic effects by reducing p65- and p52-DNA-binding and Akt-mediated JNK and ERK signaling pathways, which inhibit MMP-9 transcription [36]. …”
Section: Discussionmentioning
confidence: 99%
“…Melatonin was found to suppress the transactivation of MMP-9 and the metastasis of renal cell carcinoma (the most lethal of all urological malignant tumors with the potent metastasis potential) via the inhibition of Akt-MAPKs pathway and NF-κB DNA-binding activity [242]. Additionally, melatonin showed its oncostatic, antimetastatic and antiangiogenic effects in breast cancer both in vitro and in vivo by blocking proliferation of tumor cells and inhibiting the expression of Rho-associated kinase protein (ROCK-1), one of the regulatory and effector molecules in charge of migration/invasion, which could promote tumor growth and metastasis when its expression was increased [235].…”
Section: Bioactivities Of Melatoninmentioning
confidence: 99%